FLEXIBILITY AND ADAPTABILITY OF DOMESTICSPACEBASEDON EVERYDAY ARCHITECTURE - Bramasta Putra Redyantanu (Ide dan Dialog Desain Indonesia (Idealog), 2023)
This paper aims to discuss the idea of forming flexible and adaptive architecture for variousscenarios through the perspective of everyday architectural knowledge. The background of this study is basedon the issue and phenomenon of the development of housing to be more varied than just a living space, but also various other additional functions during a pandemic. Multiple activities outside the home are nowpart of the domestic activities themselves. A study of a residential building design illustrates howeverydayoperations reflect the adaptability and flexibility of domestic space. The exploration and analysis of the studyobject are presented through the redrawing of the space configuration along with the trajectory of dailyactivities. The connection between space, time, and users is described as a daily practice that has thepotential to develop future design methods. The findings of this qualitative study are to see how the process of forming adaptive and flexible architecture. Domestic architecture can show the dynamics of space rather thanjust the static configuration visible. The findings of this study include at least three aspects, makingtheeveryday space, using the everyday, and the configuration that is the extra ordinary. Reflections fromthisstudy show the expansion of architectural design practices that need to pay attention to the ability of spacetobe adaptive and flexible based on dynamic everyday life. Keywords : everyday architecture, domestic architecture, flexible adaptive architecture